CONTEMPORARY MARRIAGE AND SEXUAL PROBLEMS IN COMMUNITY LIFE FROM AN ISLAMIC LAW POINT OF VIEW - meirison, meirison; Pramesty, Nurika; Guchi, Rani Amelia (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2022)
This paper aims to discuss contemporary problems precisely according to the contents of our article entitled recent issues in social life. Today, the current issues continue to develop following changes in increasingly sophisticated technology and global development. In modern times, there are many contemporary problems in society, such as marriage contracts by telephone, underhanded marriages, family planning and limiting the number of children, marrying pregnant women for adultery, homosexuals and lesbians, monogamy, and polygamy. The data has been verified previously by conducting a literature study, a qualitative approach, and descriptive analysis. From data processing with this method, a finding was obtained that Muslims must be able to think rationally and critically to address such matters and the need to revisit solutions according to Islamic law to solve these problems. Contemporary problems are not far removed from the classic problems faced by the previous Ulama, which have been discussed in the classic books they have written, such as the LGBT issue, issues around marriage such as birth control or family planning, and many other problems that fatwas can answer. Fatwas and fiqh opinions existed in the classical period, which only changed the social dimension and perspective in modern times. Keywords: problems, contemporary, life, society, fiqh